Principal's Leadership In Implementing The Independent Curriculum To Improve The Quality of Learning at SMAN 1 Labuhanhaji and SMAN Unggul Darussalam Labuhanhaji South Aceh - Syarifuddin Syarifuddin; Niswanto Niswanto; Ismail Ismail (Asian Journal of Social and Humanities, 2024)
The principal's leadership is the ability and authority to influence, mobilize and direct action and encourage the emergence of a strong will with enthusiasm and confidence of teachers, staff and students in carrying out their respective duties for the progress and inspiring the school in improving learning. The purpose of this study is to find out how the leadership of school principals in implementing the independent curriculum to improve the quality of learning at SMAN 1 Labuhanhaji and SMAN Unggul Darussalam Labuhanhaji. This research uses a qualitative approach with a descriptive type of research. Based on the research findings, it was found that: (1) The planning process is carried out through meetings held at the end of each school year or before the start of the new school year. The parties involved in this planning are the principal, school superintendent, vice principals, teachers, and school committee; (2) The implementation strategy is already on the basis of a very good, effective and efficient concept. The implementation strategy is carried out through: guidance and workshops, education and training, MGMP, motivation, and through control; (3) Obstacles experienced by school principals, namely: teachers who lack mastery of material related to the independent curriculum, lack of infrastructure, workshops that are not on target, lack of funding, and lack of teacher motivation to upgrade knowledge; (4) Evaluation is carried out by determining the focus of evaluation, resource persons, assessment instruments, data collection and final reports, through questionnaires and observations / direct interviews that are routinely conducted. The parties involved in this evaluation are high school supervisors, principals, and vice heads of curriculum.